POTRET USAHATANI PADI SAWAH PADA PETANI PENGGUNA POWER THRESHER DAN COMBINE HARVESTER - Wijaya, Wijaya; Irfan Riyanto; Lusia Cipto Astuti (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
This research aims to determine the portrait of lowland rice farming among farmers who use Power Thresher and Combine Harvester. The population in this study were 64 lowland rice farmers in Dawuan Village, Tengah Tani District, Cirebon Regency. Data collection was carried out through a census of all members of the population of 64 farmers consisting of 22 farmers using the Power Thresher and 42 farmers using the Combine Harvester using a questionnaire. The results of the research showed that for farmers who used the power thresher grain thresher machine the average harvest cost per hectare was IDR. 4,719,415,- while the total cost of farming is Rp. 15,588,904,- with receipts of Rp. 25,678,143,- and farming income of Rp. 10,089,239,- For farmers who use a combine harvester grain thresher, the average harvest cost per hectare is Rp. 2,239,442 while the total cost of farming is Rp. 13,089,334,- with receipts of Rp. 28,298,792,- and farming income of Rp. 15,209,459,-. The use of a combine harvester grain threshing machine can significantly reduce harvest costs. Keywords: Farming, Power Thresher, Combine Harvester.